Estimating Structural Models of Equilibrium and Cognitive Hierarchy Thinking in the Field: The Case of Withheld Movie Critic Reviews - Brown, Alexander L.; Camerer, Colin F.; Lovallo, Dan (Management science, 2013)
Film studios occasionally withhold movies from critics before their release. Because the unreviewed movies tend to be below average in quality, this practice provides a useful setting in which to test models of limited strategic thinking: Do moviegoers seem to realize that no review is a sign of low quality? A companion paper showed that in a set of all widely released movies in 2000-2009, cold opening produces a significant 20%-30% increase in domestic box office revenue, which is consistent with moviegoers overestimating quality of unreviewed movies (perhaps due to limited strategic thinking). This paper reviews those findings and provides two models to analyze this data: an equilibrium model and a behavioral cognitive hierarchy model that allows for differing levels of strategic thinking between moviegoers and movie studios. The behavioral model fits the data better, because moviegoer parameters are relatively close to those observed in experimental subjects. These results suggests that limited strategic thinking rather than equilibrium reasoning may be a better explanation for naïve moviegoer behavior. This paper was accepted by Brad Barber, behavioral economics.